PENGARUH KHOTBAH DALAM IBADAH MINGGU TERHADAP KEDEWASAAN IMAN JEMAAT DI GKSI MERAUKE - Jansakti Saddu Saly; Hasahatan Hutahaean (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2020)
This study aims to determine the effect of sermons in Sunday worship on the maturity of the congregation's faith in the Gereja Kristen Indonesia Setia (GKSI) Merauke. The method used is quantitative. The hypothesis is that there is a positive and significant influence between the sermon in Sunday worship on faith maturity. The population is the GKSI Merauke congregation, amounting to 292 people with a sample of 30 people. The instrument used was a closed questionnaire. Validity is tested using the product-moment correlation formula. Data were analyzed using the correlation technique (rxy), tested for the significant relationship with the formula (t) and the test of determination (r2), and simple regression. The successful test was tested by F, and then to find out the effect regression equation was carried out with the formula Y = a + bX. The results showed the effect or r2 = 51% and significant influence or F count = 28.65 where it is known that F table = 4.17 and obtained the meaning of the simple regression equation Y = 7.25 + 0.87X. This study concludes that the sermon on Sunday worship positively and significantly affects the congregation's faith maturity.